2006
DOI: 10.1159/000089302
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Catheter Placement for Fetal Cystic Adenomatoid Pulmonary Malformation: A Case Report

Abstract: Introduction: Fetal congenital cystic adenomatoid malformation is a pulmonary developmental anomaly arising from an overgrowth of the terminal respiratory bronchioles. This is such a rare malformation that it is not always thought of as a diagnostic possibility. Case: In the present case, after a large pulmonary cyst started deviating the mediastinum and following an increase in amniotic fluid volume in the fetus at 28 weeks of gestation, the placement of a catheter for continuous drainage was performed. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The literature review identified another 18 fetuses with a large cyst causing major mediastinal shift that were treated by placement of a thoracoamniotic shunt (Table 5)1–3, 6, 74, 85–90. In five of these fetuses, thoracentesis was first performed, with subsequent rapid reaccumulation of fluid within the cyst.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review identified another 18 fetuses with a large cyst causing major mediastinal shift that were treated by placement of a thoracoamniotic shunt (Table 5)1–3, 6, 74, 85–90. In five of these fetuses, thoracentesis was first performed, with subsequent rapid reaccumulation of fluid within the cyst.…”
Section: Resultsmentioning
confidence: 99%
“…The infant underwent uneventful postnatal resection of the CPAM. To date, at least 28 CPAMs have been managed by thoracoamniotic shunting, with about a 70% survival [19,21,22,50,56,57,[59][60][61]. It is, however, important to note that despite successful prenatal cyst decompression, these infants often have significant pulmonary hypoplasia and mass effect at birth.…”
Section: Prenatal Diagnosis and Natural Historymentioning
confidence: 99%
“…If there are any dominant cysts, even with a CVR <1.6, there is a risk of acute cyst growth and development of fetal hydrops. A thoracoamniotic shunt may be considered if signs of fetal decompensation at <32 weeks’ gestation are identified 15 . Microcystic lesions increase the risk of fetal hydrops, pulmonary hypoplasia, and polyhydramnios 16 .…”
Section: Discussionmentioning
confidence: 99%